Epistemologi Islamisasi Ilmu Pengetahuan dalam Pemikiran Ismail Raji Al-Faruqi - Muhammad Qasim; Muhammad Rusydi; Hasbi Siddik (Sipakatau: Jurnal Pendidikan dan Kebudayaan, 2025)
This research article focuses on examining the concept of the epistemology of the Islamization of knowledge in the thought of Ismail Raji al-Faruqi. Through a library-based study that analyzes various relevant scholarly sources, it is found that al-Faruqi’s epistemology of the Islamization of knowledge is oriented toward tawhid as the epistemological principle underlying the entire process of the production, validation, and application of knowledge; rejects the dichotomy between secular and religious knowledge by eliminating the notion of value-free science through the integration of Islamic values into every epistemic step; emphasizes the integration of revelation and reason by positioning both as mutually complementary sources, structures, methods, and standards of epistemic validity; and views knowledge as an instrument for realizing human well-being and public good.